IMPROVING STATE REGULATION AND MANAGEMENT MECHANISMS TO ENHANCE THE POTENTIAL OF PILGRIMAGE TOURISM - Ergashev Rakhmatulla , Khidirovich; Uzakov Jamshid , Norboevich (THE INNOVATION ECONOMY, 2025)
This article focuses on analyzing the role of state regulation and management mechanisms in enhancing the potential of pilgrimage tourism in Uzbekistan. The study examines the economic, social, and cultural significance of pilgrimage tourism, the current state of the sector, and challenges related to infrastructure, safety, and service quality. Based on Uzbekistan’s experience and international practices, including models from Saudi Arabia and Turkey, the effectiveness of state policies is evaluated. The findings highlight the need for a balanced approach rooted in the synthesis of state and market mechanisms in regulating pilgrimage tourism. The article proposes measures to expand public-private partnerships, implement digital management systems, and strengthen international cooperation.